Comparative analysis of mini-open trans-thoracic transpleural and posterior approaches in thoracic disc herniation surgery: A 10-year retrospective review - Ali Baram; Giorgio Cracchiolo; Marco Riva; Gabriele Capo; Leonardo Anselmi; Carlo Brembilla; Stefania Radice; Maria Pia Tropeano; Carla Anania; Emanuela Morenghi; Maurizio Fornari; Federico Pessina (Brain and Spine)
Introduction: Thoracic disc herniations (TDHs) are rare, and surgery is typically reserved for patients with radiculopathy, myelopathy, or intractable back pain. Despite established algorithms, the optimal surgical strategy remains debated. Research question: What are the clinical, surgical, and radiological outcomes of anterior and posterior surgical approaches for TDHs over a 10-year period? Material and methods: A retrospective analysis of 54 patients who underwent surgery for TDHs (2013–2022) was performed. Patients were grouped by surgical approach: anterior (34 patients) and posterior (20 patients). Data included preoperative and postoperative outcomes such as operative times, hospital stays, complications, reoperations, and assessments using the Frankel scale, Nurick score, and Visual Analog Scale (VAS) for pain. Results: Both approaches improved clinical outcomes. No significant differences in postoperative Nurick or VAS pain scores were observed. However, the anterior approach showed better Frankel score improvements but was associated with longer operative times and hospital stays. Complications were more frequent in the anterior group. Discussion and conclusion: Both approaches effectively alleviate symptoms in symptomatic TDHs. The anterior approach offers greater neurological improvement but carries higher complication risks. Surgical strategy should be tailored based on herniation characteristics and surgeon expertise. Anterior approaches are ideal for central, large, or calcified herniations, while posterior approaches are preferable for lateral ones.